DAMPAK MARKETING MIX “PHYSICAL ENVIRONMENT” TERHADAP KEPUASAAN PASIEN RUMAH SAKIT: LITERATURE REVIEW - Safi’i, Akhmad; Nugroho, Bagus; Kirana, Irin; Muhammadi, Muhammadi; Kamaluddin, Rachmat; Damanik, Regina Destrina; Sulistiadi, Wahyu (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2021)
Marketing mix strategy is a necessary strategy in service organizations to ensure successful performance. One of the successful performance is measured by patient satisfaction. Patient satisfaction is considered as one of the most important predictors when measuring outcomes and quality of services provided by health facilities. From patient satisfaction obtained loyalty, patient compliance, and has a direct impact on hospital income. This article is built with a literature review obtained from a search database from pubmed and google scholar using the keywords "marketing mix" AND "hospital" AND "impact". The included articles explain the relationship between the marketing mix, especially the physical environment, and patient satisfaction. From 258 articles found 5 relevant articles. 4 articles (80%) used a cross sectional study design and 1 article (20%) used a survey. All articles come from the Asian region, 3 from Indonesia (60%), the rest each from Iran and Saudi Arabia. 4 articles describe the marketing mix of product variables, people or officers, physical evidence, prices, and promotions that affect patient satisfaction. 1 article tells that the marketing mix has not been maximally implemented in government hospitals compared to private hospitals. Based on the analysis of previous studies, it can be concluded that the marketing mix is important and has a significant effect on patient satisfaction.